Determinants of youth unemployment in Southern Ethiopia: Evidence from Duna District, Ethiopia - Tamirat, Negese (Goodwood Publishing, 2023)
Purpose: Unemployment is a big problem both in developed and less developed countries. This study was aimed at investigating the determinants of youth unemployment in Duna district using cross-sectional survey data gathered in 2020. It is assumed to be a major macroeconomic problem in deriving economic growth and food security. Reducing youth unemployment is crucial to achieving sustainable economic development and alleviating poverty. Research methodology: Multi-stage sampling methods were developed to select the sample from a given population. Through considering the availability of youth unemployed, six kebeles with a sample youth of 361 were selected. Primary and secondary sources of data were used. Descriptive analysis and binary logistic regression were employed for the data analysis. Results: The results of binary logit regression revealed that youth unemployment was significantly affected by age, sex, educational status (secondary and higher education), cultivated land size, marital status, credit use, information use, family wealth, infrastructure, work experiences, and migration. Limitations: This research is limited by the scope, men, and women young unemployed were not equally studied. Without inclusion, women in the studies may not ensure sustainable economic development and alleviate the problem of young unemployment and poverty. Contribution: Ministry of youth, sports and culture, microfinance institutions, and other concerned bodies should give important attention to youth unemployment which is a major problem in achieving economic growth and alleviating poverty. Reduction in the level of youth unemployment would consequently improve youth income and which in turn improve living standards.